Determining the technical and economic parameters for designing hybrid power units for the budget segment - Smyrnov, Oleh; Borysenko, Anna; Trynova, Irina; Levchenko, Iaroslava; Marchenko, Anton (Eastern-European Journal of Enterprise Technologies, 2020)
The paper addresses the issue of designing environmentally friendly and energy-efficient vehicles in a budget segment based on determining the technical-economic parameters. The fuel efficiency and environmental friendliness of cars have been improved and substantiated through devising a hybrid power system based on the chosen rational technical-economic parameters. We have constructed three-dimensional dependences of energy, consumed by the unit of traction rechargeable batteries, and a relative travel range, on the mass and steady speed. Recommendations have been made on selecting the energy intensity of the unit of traction rechargeable batteries for hybrid vehicles of different mass and the desired travel range under an electricity-only mode. We have established the travel range under an electricity-only mode per a single charge of traction rechargeable batteries within 20 km to 50 km. The choice of a hybrid vehicle has been proposed depending on the expected average daily mileage and the energy intensity of traction rechargeable batteries. This would make it possible for a consumer to make a decision about the choice of a hybrid vehicle based on the individual planned average daily mileage. Conceptual solutions have been developed to construct hybrid power units based on the economic principle of their design. The scientific results have been confirmed in practice using an experimental hybrid concept based on the ZAZ Lanos Pickup. Such an approach makes hybrid vehicles more competitive and economically attractive